1995
DOI: 10.1007/bf01294804
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive stabilised and pure flip chips on various substrates under thermocycling

Abstract: The paper presents numerical simulations and experimental investigations on flip chip modules having silicon, alumina ceramics, polyimide or polyester foil, or epoxy glass laminates as substrate material under thermo cycle test conditions. Some of the flip chip modules were stabilised additionally by filling the remaining gap between chip and substrate with an epoxy underfiller. The presented results concern the stress distribution in the joints as basis of their shape optimisation for the modules without unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The stresses generated due to the CTE mismatch of the materials may lead to warpage [10] in the assembly. The thermally-induced warpage directly affects the interconnection between the chip and the substrate, causing poor integrity in the assembly [11]. During thermally-induced warpage, the conductive particles in the ACF, which provide the actual interconnection path, experience different types of stresses.…”
Section: Contact Resistance Of Acf Jointsmentioning
confidence: 99%
“…The stresses generated due to the CTE mismatch of the materials may lead to warpage [10] in the assembly. The thermally-induced warpage directly affects the interconnection between the chip and the substrate, causing poor integrity in the assembly [11]. During thermally-induced warpage, the conductive particles in the ACF, which provide the actual interconnection path, experience different types of stresses.…”
Section: Contact Resistance Of Acf Jointsmentioning
confidence: 99%
“…6(b) has not yet failed, although cracks in the solder material can clearly be observed. The investigations of the cross sections revealed that the solder material has separated into a "layered" structure of Snand Pb-rich phases, and it was discovered that cracking in most cases occur in the interface between the two phases [8], as illustrated by Fig. 6(a).…”
Section: B Samples With Underfill a (Without Filler)mentioning
confidence: 99%
“…Also, apart ftom the ahovementioned parameters, the presence of stresses in the form of residual stresses, or stresses developed during thermal cycling has a profound influence on the joint efficiency and its durability. In electronic devices, cyclic stress manifests itself through the thermal mismatch between the chip and the substrate, which in tum limits the lifetime of the joint [4,5, 6,7].…”
Section: Introductionmentioning
confidence: 99%